La distinción entre “hecho” y “acción” frente al “derecho del saber”. Agencia, imputación y suerte en la Rechtsphilosophie de Hegel - Mañalich R., Juan Pablo (2023)
This article reconstructs the notion of action that, anchored in a wider account of imputation practices, Hegel develops in the “Morality” chapter ofhis Philosophy of Right, beginning with a preliminary clarification of what it means that “crime” designates something that has the status of an action. Considering a set of premises found in some recent analytically oriented interpretations of Hegel’s work developed by Robert Brandom and Michael Quante, I examine the distinction proposed by Hegel between the concepts of deed and action, to then clarify the meaning of the “·right of knowledge” and its relationship to the “right of intention”. This enables one to make explicit the particular form of “compatiblism” that can be extracted from Hegel’s philosophy as a way to face the problem of moral luck.